Development of low-alcohol isotonic beer by interrupted fermentation - De Fusco, Deborah Oliveira [UNESP]; Madaleno, Leonardo Lucas; Del Bianchi, Vanildo Luiz [UNESP]; Bernardo, Aline da Silva; Assis, Rafael Roberto; de Almeida Teixeira, Gustavo Henrique [UNESP] (Oxford University Press (OUP), 2019)
Alcohol-free beer with isotonic properties is getting more popular and its production can be carried out by different production strategies; however, interrupted fermentation is still a challenge. Therefore, the objective of this study was to develop a low-alcohol isotonic beer (<0.5% v/v) by interrupted fermentation. Moreover, the major objective is to compare the developed product to commercial beverages (sports drinks, ‘Pilsen' regular beer, alcohol-free beers and low-alcohol isotonic beer). The beverages were evaluated based on pH, alcohol content (% v/v), total titratable acidity (mEq L−1), osmolality (mOsmol kg−1), bitterness International Bitterness Units, colour European Brewery Convention, total phenolic compounds (mg L−1 gallic acid), reducing and total sugars (%) and Na and K contents (mg L−1). The developed low-alcohol isotonic beer presented characteristics similar to sports drinks, with the advantage of being richer in phenolic compounds and suitable osmolality. Despite salts were added in its formulation, the grades attributed to all beers employed in the sensory evaluation, as well as the purchase intention did not present significant differences.
Keywords: Isotonic; low-alcohol beer; osmolality; sports drinks